832 Examining coastal drowning fatalities in the Republic of Ireland, 2010–2013. (1st September 2016) - Kervick, Aoife; Dix, Dani; Walters, Thomas; Sweeney, Roger; Sarma, Kiran
Abstract : Background: On average, 135 people drown in the Republic of Ireland (ROI) every year. There is growing recognition that coastal drowning fatalities in particular are a significant health concern. In order to inform the design of targeted prevention strategies for coastal areas in the ROI, this research study sought to enhance and augment current coastal drowning fatality records, and produce detailed statistical estimates in relation to these deaths. Methods: A coastal drowning dataset was compiled. To enhance data records, complimentary sources were investigated, including data from the Royal National Lifeboat Institution (RNLI) and media reports. Unique coastal fatality cases were identified by location, name of victim (where possible), date of incident, and/or other identifiers as needed (such as age, gender). The fatality cause was then classified (e.g. due to accident, suspected self-harm etc.), and data analysed. Results: Complimentary data sources improved the scope of initial records from documenting 70 coastal drowning fatalities, to records for 198 that occurred during this time period. Overall, coastal drowning deaths accounted for approximately 39% of all drowning fatalities that occurred in the ROI during 2010–2013. The majority of these were accidental deaths (48%), unspecified incidents (26.3%), due to suspected self-harm (24.7%), natural causes (0.5%) or assault (0.5%). Where gender and age were documented, it was found that males comprised 82% of fatalities ( n = 124), and that those aged between 30–69 years accounted for 81% ( n = 104) of coastal drowning deaths. Conclusions: Coastal drowning fatalities accounted for approximately 40% of all drownings that occurred in the ROI during 2010–2013. Findings suggest that coastal drowning interventions should focus on targeting males, and those above 30 years of age.